2014
DOI: 10.1523/jneurosci.2282-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Bihemispheric Transcranial Direct Current Stimulation Enhances Effector-Independent Representations of Motor Synergy and Sequence Learning

Abstract: Complex manual tasks-everything from buttoning up a shirt to playing the piano-fundamentally involve two components: (1) generating specific patterns of muscle activity (here, termed "synergies"); and (2) stringing these into purposeful sequences. Although transcranial direct current stimulation (tDCS) of the primary motor cortex (M1) has been found to increase the learning of motor sequences, it is unknown whether it can similarly facilitate motor synergy learning. Here, we determined the effects of tDCS on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
118
3
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(133 citation statements)
references
References 74 publications
11
118
3
1
Order By: Relevance
“…-pressing a keyboard key or button), while the required sequence of actions are typically complex in structure (between 8-15 items in length with controls on smaller intra-sequence patterns). Alternatively, the SVIPT requires execution of a precision pinch force action that is more difficult to elicit than a key-press (Waters-Metenier, Husain, Wiestler, & Diedrichsen, 2014). Thus, there is a greater emphasis placed upon accurate performance of the unit action within an explicit sequence context in the SVIPT than most variants of SFTTs.…”
Section: Motor Learningmentioning
confidence: 99%
See 4 more Smart Citations
“…-pressing a keyboard key or button), while the required sequence of actions are typically complex in structure (between 8-15 items in length with controls on smaller intra-sequence patterns). Alternatively, the SVIPT requires execution of a precision pinch force action that is more difficult to elicit than a key-press (Waters-Metenier, Husain, Wiestler, & Diedrichsen, 2014). Thus, there is a greater emphasis placed upon accurate performance of the unit action within an explicit sequence context in the SVIPT than most variants of SFTTs.…”
Section: Motor Learningmentioning
confidence: 99%
“…Several studies, a majority of which have focused on sequence learning, have investigated offline motor skill learning and retention over multiple (typically at least three) days of training (Table 2) (Cantarero et al, 2015;Naros et al, 2016;Reis et al, 2015;Reis et al, 2009;Saucedo-Marquez, Zhang, Swinnen, Meesen, & Wenderoth, 2013;Schambra et al, 2011;Waters-Metenier et al, 2014). Reis and colleagues (2009) found that anodal tDCS applied to M1 concurrently with training over five consecutive days resulted in significant enhancement of offline skill gains and retention compared with sham in the sequential visual isometric pinchforce task (SVIPT) (Reis et al, 2009).…”
Section: Offline Motor Skill Learning and Retentionmentioning
confidence: 99%
See 3 more Smart Citations